Window, Dr. Bhau Daji Lad Museum - Ghosh, Ayan (2023)
Dr. Bhau Daji Lad Museum was designed by William Tracey in the Neo-Palladian style that originated in Italy. From 2003–08, the Indian National Trust for Art and Cultural Heritage (INTACH) in collaboration with the Jamnalal Bajaj Foundation and the Brihanmumbai Municipal Corporation undertook extensive refurbishment of the building.